2009
DOI: 10.1080/09687630701741030
|View full text |Cite
|
Sign up to set email alerts
|

Mental health problems: Are they or are they not a risk factor for dropout from drug treatment? A systematic review of the evidence

Abstract: Background: A sizeable number of recent studies investigating whether clients with substance misuse

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 79 publications
1
17
2
Order By: Relevance
“…This is the first study, to our knowledge, to set out to discover whether personality functioning as measured through characteristic adaptations might assist in the identification of potential obstacles to treatment engagement in substance misuse treatment. The evidence provided in this study is broadly consistent with, and extends, previous studies in diverse clinical populations which found that personality functioning was associated with differential responses to treatment [28], with maladaptive levels predicting poorer treatment response [29] and non-engagement [30,31]. High levels of emotional dysregulation had also previously been found to be associated with non-compliance, denial and behavioural disengagement [41].…”
Section: Discussionsupporting
confidence: 89%
“…This is the first study, to our knowledge, to set out to discover whether personality functioning as measured through characteristic adaptations might assist in the identification of potential obstacles to treatment engagement in substance misuse treatment. The evidence provided in this study is broadly consistent with, and extends, previous studies in diverse clinical populations which found that personality functioning was associated with differential responses to treatment [28], with maladaptive levels predicting poorer treatment response [29] and non-engagement [30,31]. High levels of emotional dysregulation had also previously been found to be associated with non-compliance, denial and behavioural disengagement [41].…”
Section: Discussionsupporting
confidence: 89%
“…Research into mental health services utilization by patients with COD has yielded mixed findings; however, a major limitation of many studies focused on this subject is the exclusion of patients with acute and severe mental disorders. 31 Furthermore, previous studies analyzing the effect of psychiatric symptom severity on service utilization 32,33 have also found a direct association between these two variables. This may be explained by the increase in interpersonal difficulties at higher levels of disease severity, which may lead to difficulty receiving feedback and instructions from the clinician, 34 or by higher levels of self-stigma and internalized shame, which reduce overall participation in mental health services.…”
Section: Discussionmentioning
confidence: 99%
“…Minimum stays of 90 days are now required in the UK as indicators for treatment effectiveness (National Treatment Agency (NTA), 2006a). A recent systematic review by Meier and Barrowclough (2009) included 58 studies published since 1990 that investigated the relationship of co-morbid problems and treatment retention. Except for clients with antisocial personality disorder, the reviewers concluded that, overall, the evidence does not support the common belief that DD clients are at a higher risk of dropout from addiction treatment than other substance misuse clients in general.…”
Section: Introductionmentioning
confidence: 99%